Correction to: The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D (Acta Neuropathologica Communications, (2023), 11, 1, (129), 10.1186/s40478-023-01618-6) - Wang, Dan Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De Hong; Coras, Roland; Wang, Yu Jiao; Shi, Jie; Zhou, Wen Jing; Kobow, Katja; Piao, Yue Shan (Acta Neuropathologica Communications, 2024)
Following publication of the original article [1], the authors identified errors in the reference list and citations. Due to a technical error a wrong article version for the references and citations was used. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2024-04-05